TERT promoter mutations and methylation for telomerase activation in urothelial carcinomas: New mechanistic insights and clinical significance - Liu, Tiantian; Li, Shihong; Xia, Chuanyou; Xu, Dawei (Frontiers in Immunology, 2023)
Telomerase, an RNA-dependent DNA polymerase synthesizing telomeric TTAGGG sequences, is primarily silent in normal human urothelial cells (NHUCs), but widely activated in urothelial cell-derived carcinomas or urothelial carcinomas (UCs) including UC of the bladder (UCB) and upper track UC (UTUC). Telomerase activation for telomere maintenance is required for the UC development and progression, and the key underlying mechanism is the transcriptional de-repression of the telomerase reverse transcriptase (TERT), a gene encoding the rate-limiting, telomerase catalytic component. Recent mechanistic explorations have revealed important roles for TERT promoter mutations and aberrant methylation in activation of TERT transcription and telomerase in UCs. Moreover, these TERT-featured genomic and epigenetic alterations have been evaluated for their usefulness in non-invasive UC diagnostics, recurrence monitoring, outcome prediction and response to treatments such as immunotherapy. Importantly, the detection of the mutated TERT promoter and TERT mRNA as urinary biomarkers holds great promise for urine-based UC liquid biopsy. In the present article, we review recent mechanistic insights into altered TERT promoter-mediated telomerase activation in UCs and discuss potential clinical implications. Specifically, we compare differences in senescence and transformation between NHUCs and other types of epithelial cells, address the interaction between TERT promoter mutations and other factors to affect UC progression and outcomes, evaluate the impact of TERT promoter mutations and TERT-mediated activation of human endogenous retrovirus genes on UC immunotherapy including Bacillus Calmette-Guérin therapy and immune checkpoint inhibitors. Finally, we suggest the standardization of a TERT assay and evaluation system for UC clinical practice.